Causes for Disruptive Behaviors in ECE Children of Public Primary Schools: A Qualitative Case Study - Mahnoor (JIE, 2025)
This research case study aimed to explore the causes of disruptive behaviors in students of a public primary school of Tehsil Sarai Alamgir. Utilizing a qualitative approach, the study conducted semi-structured interviews comprising of open-ended questions to achieve comprehensive insights. Data was collected from parents of grade two students, then it was transcribed to analyze with NVivo 12 software to understand the underlying causes and impacts. The findings highlighted key parental influences in mitigating these behaviors. This research provides a detailed evaluation of the causes of prevalence of disruptive behaviors among early graders. Through a deeper investigation involving parents, it was discovered that these behaviors often manifest differently at home, with some hidden tendencies emerging that were not as evident in the school environment. Parents identified a broad range of causes contributing to these behaviors.